2021
DOI: 10.1007/s40201-021-00659-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ambient black carbon and daily mortality in Tehran, Iran: a distributed lag nonlinear time series analysis

Abstract: Purpose The aim of the present study was to investigate the effect of short-term exposure to ambient black carbon (BC) on daily causespecific mortality, including mortality due to respiratory, cardiovascular, ischemic heart and cerebrovascular diseases in Tehran, Iran. Materials and methods Daily non-accidental death counts, meteorological data and hourly concentrations of air pollutants from 2014 to 2017 were collected in Tehran. A distributed lag non-linear model was used to assess the association between ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Of these, 70 fulfilled the inclusion criteria (figure 1). 7 21–26 34–96 Of the 70 included studies, 56 estimated the short-term effects of BC/EC using a time series design or case cross-over design, while 14 studies explored the long-term effects of BC/EC using a cohort design. Thirty-seven of the 70 studies reported morbidity as the outcome variable, 25 studies reported mortality and 8 studies reported both morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 70 fulfilled the inclusion criteria (figure 1). 7 21–26 34–96 Of the 70 included studies, 56 estimated the short-term effects of BC/EC using a time series design or case cross-over design, while 14 studies explored the long-term effects of BC/EC using a cohort design. Thirty-seven of the 70 studies reported morbidity as the outcome variable, 25 studies reported mortality and 8 studies reported both morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the majority of the included studies on the exposure assessment were assessed as ‘probably low’ and ‘probably high’, and in some cases studies were rated as ‘high’ risk. Three studies were rated as ‘high risk’ on exposure assessment mainly because pollutants were measured with a single monitoring over a large geographical area, and not measured at least daily 53 85 92…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the interquartile range for BC (2.7 mg/m 3 ) corresponded to increases in total, cardiovascular, and respiratory mortality of 2.3%, 3.2%, and 0.6%, respectively [12]. Some studies have shown that BC accelerates the formation of atherosclerotic plaques, suggesting long-term effects on cardiovascular health [11,13]. BC is thought to be inextricably linked to pneumoconiosis and is Sustainability 2023, 15, 12828 2 of 17 associated with increased respiratory symptoms, a slight decrease in lung function, and the accumulation of dust in the lungs [14,15].…”
Section: Introductionmentioning
confidence: 99%